Performance and Attitude of Dental Poly Officers with Patient Satisfaction on JKN Era in Panembahan Hospital Bantul Yogyakarta - Naufal Rachmanda; Edi Sumarwanto; Ayu Kristin Rakhmawati (Jurnal Kesehatan Gigi, 2019)
Panembahan Senopati Hospital is a referral hospital. In the government program in the form of the National Health Insurance (JKN), most people who seek treatment at Panembahan Senopati District Hospital have health insurance. The ineffectiveness of the referral system in Indonesia has an impact on the accumulation of patients in advanced health facilities, resulting in a decline in the quality of health services provided. The main indicator of knowing hospital standards is patient satisfaction with services from the hospital. Various facts show that there are serious problems in the quality of health services in Indonesia. This is due to the absence of the best quality control system that can be applied. To determine the level of satisfaction of National Health Insurance (JKN) patients with the quality of health services provided by dental clinic officers at Panembahan Senopati Hospital. Descriptive analytic observational with a cross sectional study design. The population in this study were patients who received dental and oral health services. Samples were taken using 86 accidental sampling techniques. Data was collected using a questionnaire consisting of 14 structured question items based on the performance and attitude of dental clinicians. Data analysis using the Chi-Square test followed by logistic regression test. From the results of multivariate analysis, the P value of 0.035 performance is significant and has a greater chance of 10,588 times compared to performance that is not appropriate. P value of 0.023 attitude is significant and has a 4.315 times the opportunity compared to attitudes that do not include 3 components. Factors related to satisfaction include intelligence, skills. emotional stability, a person's characteristics include attitudes, personal traits, physical traits, desires and motivation. There is a relationship between the performance and attitude of dental clinicians that performance is a variable X which is more influential with a value of P = 0.035 compared with attitude with a value of P = 0.023 to the variable Y about patient satisfaction of dental dentists.